Implementasi Kebijakan Padat Karya Tunai (PKT) pada Masyarakat Miskin di Desa Lebih, Gianyar - Anak Agung Gde Rai Budiasa; A. A. Gde Raka; I Made Mardika (Public Inspiration : Jurnal Administrasi Publik, 2019)
Abstract Cash intensive work (PKT) is an activity of empowering poor families that is productive by utilizing appropriate resources and technology in reducing poverty, increasing income, and reducing stunting, through self-management, prioritizing local workforce and materials. Lebih Village as a research object with consideration, namely as a tourism area and is near to the government center. This research is entitled "Implementation of Cash Intensive Work Policy in Poor Communities in the Lebih Village, Gianyar". Formulation of research problems, namely: 1) How is the implementation of cash intensive work policy in Lebih Village, Gianyar? 2) Are the supporting factors and constraints of the cash intensive work policy implemented in Lebih Village, Gianyar and 3) What is the impact of the implementation of the cash intensive work policy on the poor in Lebih Village, Gianyar? The theories used are Merilee S. Grindle's, Edwards III, and Jan Mersee's. The research approach uses a qualitative descriptive approach. The technique of determining informants using purposive sampling. Data collection techniques using observation, interviews, and documentation. Data analysis technique is qualitative descriptive data analysis, including data reduction, data display, conclusions and verification. The results of the study concluded that 1) The implementation of the cash intensive work policy in Lebih Village, where the cash intensive work can be implemented well such as : implementing priority activities using the Village Fund; implementation of cash intensive work activities in a self-managed manner; payment of wages in cash; and the involvement of the community as implementers of self-management. 2) Supporting factors for cash intensive work policy, include: Government policies, village institutions, labor availability and types of work, as well as inhibiting factors for cash intensive work policy, including: harmonizing village planning and worker expertise. 3) The impact of cash intensive work policy implementation on the poor in Lebih Village, Gianyar, including: economic, social and cultural impacts. Keywords: Cash Intensive Work; Policy Implementation; Poor Communities Abstrak PKT merupakan kegiatan pemberdayaan keluarga miskin bersifat produktif memanfaatkan sumber daya dan teknologi tepat guna dalam mengurangi kemiskinan, meningkatkan pendapatan, dan menurunkan angka stunting, melalui swakelola, mengutamakan tenaga kerja dan material lokal. Desa Lebih sebagai objek penelitian, karena kawasan pariwisata serta paling dekat dengan pusat pemerintahan. Penelitian ini berjudul â€œImplementasi Kebijakan PKT pada Masyarakat Miskin di Desa Lebih, Gianyarâ€. Rumusan masalah, yaitu : 1) Bagaimana implementasi kebijakan PKT di Desa Lebih, Gianyar? 2) Apakah faktor-faktor pendukung dan penghambat kebijakan Padat Karya Tunai dilaksanakan di Desa Lebih, Gianyar?Dan 3) Bagaimana dampak implementasi kebijakan PKT terhadap masyarakat miskin di Desa Lebih, Gianyar? Teori yang digunakan adalah teori kebijakan model Merilee S. Grindle, Edwards III, dan Jan Mersee. Pendekatan penelitian menggunakan pendekatan deskriptif kualitatif. Penentuan informan menggunakan purposive sampling. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Teknik analisis data dengan analisis data deskriptif kualitatif, meliputi reduksi data, display data, penarikan kesimpulan dan verifikasi. Hasil termuan penelitian yaitu 1) Implementasi kebijakan PKT di Desa Lebih, di mana PKT terlaksana dengan baik seperti : pelaksanaan kegiatan prioritas penggunaan Dana Desa; pelaksanaan kegiatan PKT secara swakelola; pembayaran upah secara tunai; serta keterlibatan masyarakat sebagai pelaksana swakelola. 2) Faktor-faktor pendukung kebijakan PKT, meliputi : kebijakan Pemerintah, kelembagaan desa, kesediaan tenaga kerja dan jenis pekerjaan, serta faktor-faktor penghambat kebijakan PKT, meliputi : penyelarasan perencanaan desa dan keahlian pekerja. 3) Dampak implementasi kebijakan PKT terhadap masyarakat miskin di Desa Lebih, meliputi : dampak ekonomi, sosial, dan budaya. Kata Kunci: Padat Karya Tunai; implementasi Kebijakan; masyarakat Miskin